2020
DOI: 10.1021/acsami.0c16431
|View full text |Cite
|
Sign up to set email alerts
|

High Quality Factor Enabled by Multiscale Phonon Scattering for Enhancing Thermoelectrics in Low-Solubility n-Type PbTe–Cu2Te Alloys

Abstract: The fundamental challenge for enhancing the thermoelectric performance of n-type PbTe to match p-type counterparts is to eliminate the Pb vacancy and reduce the lattice thermal conductivity. The Cu atom has shown the ability to fill the cationic vacancy, triggering improved mobility. However, the relatively higher solubility of Cu2Te limits the interface density in the n-type PbTe matrix, leading to a higher lattice thermal conductivity. In particular, a quantitative relationship between the precipitate scatte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
3
5
0
Order By: Relevance
“…The integration of the reduced electrical conductivity and the improved Seebeck coefficient contributes to a tremendous enhancement of PF in the Cu-intercalated PbTe–MnTe samples, especially at room temperature, ranging from ∼2.37 mW m –1 K –2 (0.1% Cu) to ∼3.07 mW m –1 K –2 (0.5% Cu); the temperature-dependent PF for all samples can be seen in Figure S1 in Supporting Information. As shown in Figure c, compared with the experimental value reported in the literature, ,,,,, the PF of Cu-intercalated samples maintains a higher value in the whole temperature range, consistent with the theoretical prediction, but a value lower than the predicted value from another report due to the increased inertial effective mass in PbTe–MnTe alloys. In particular, the PF of Cu-doped PbTe–MnTe alloys in this work at room temperature is much higher than that of conventional np 3 donor Sb-doped PbTe–MnTe alloys, while the PF at an elevated temperature is still equivalent …”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The integration of the reduced electrical conductivity and the improved Seebeck coefficient contributes to a tremendous enhancement of PF in the Cu-intercalated PbTe–MnTe samples, especially at room temperature, ranging from ∼2.37 mW m –1 K –2 (0.1% Cu) to ∼3.07 mW m –1 K –2 (0.5% Cu); the temperature-dependent PF for all samples can be seen in Figure S1 in Supporting Information. As shown in Figure c, compared with the experimental value reported in the literature, ,,,,, the PF of Cu-intercalated samples maintains a higher value in the whole temperature range, consistent with the theoretical prediction, but a value lower than the predicted value from another report due to the increased inertial effective mass in PbTe–MnTe alloys. In particular, the PF of Cu-doped PbTe–MnTe alloys in this work at room temperature is much higher than that of conventional np 3 donor Sb-doped PbTe–MnTe alloys, while the PF at an elevated temperature is still equivalent …”
Section: Resultssupporting
confidence: 88%
“…However, all the black squares are consistent with the Pisarenko line with an effective mass of 0.36 m e . That is, there is no further enhancement in effective mass and the scattering factor in Cu-intercalated samples, indicating that the copper interstitial has little effect on the band structure and scattering mechanism, similar to other reports. , It is confirmed that the enhancement of PF of Cu-containing samples arises from the other factors and not the band structure or scattering mechanism.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Enhancements in thermoelectric performance have also been observed in polymer composites [28,29]. Similarly, many chaclogenide compounds are promising for thermoelectric applications [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 95%